Influence of Deep-Water Corals and Sponge Gardens on Infaunal Community Composition and Ecosystem Functioning in the Eastern Canadian Arctic - Pierrejean, Marie; Grant, Cindy; Neves, Bárbara de Moura; Chaillou, Gwénaëlle; Edinger, Evan; Blanchet, F. Guillaume; Maps, Frédéric; Nozais, Christian; Archambault, Philippe (Frontiers in Marine Science, 2020)
The relationships between infaunal diversity and ecosystem function of biogenic structures in the Eastern Canadian Arctic remain poorly documented. Our study investigated the influence of sponge gardens at the Frobisher Bay site (138 m) and bamboo corals at the Baffin Bay site (1007 m) on the infaunal community structure and benthic ecosystem functioning. The occurrence of both types of biogenic structure type enhanced particular taxa and/or feeding guilds. A large density of suspension filter feeders was observed in bamboo coral sediment, whereas bare sediment exhibited a large proportion of nematodes and deposit-detritus feeders. Sponge gardens’ sediment showed a high proportion of isopods, Paraonidae polychaetes and up/down conveyors whereas bare sediment exhibited a large density of filter feeders. Through incubation cores, we measured ex-situ benthic nutrient and oxygen fluxes at the sediment-water interface in each habitat and site. Biogeochemical fluxes varied significantly between habitats in the Baffin Bay site with a significant impact of bamboo coral habitat on nutrient fluxes (nitrate, ammonium and silicate). Surprisingly, the sediment hosting bamboo corals acted as a source of nitrate and ammonium reaching values similar or higher to the Frobisher site despite the difference in water depth, and thus food supply between the two sites. These significant releases could derive from (i) a high organic matter deposition in bamboo coral habitat, allowed by their erected structure, (ii) a high efficiency of bioturbators (surficial modifiers and burrowers) mixing the surface layer of the sediment and (iii) the difference in sediment type. Our study highlighted that, compared to its adjacent habitat, the presence of bamboo corals appeared to enhance the infaunal density and nutrient release of its sediment. In contrast, the impact of sponge gardens was not as clear as for bamboo coral habitat, likely due to the relatively significant presence of megabiota in the sponge garden adjacent habitat. Thus, our results based on a relatively small sample size, indicate that the bamboo coral habitat seems to increase the efficiency of deep-benthic ecosystem functioning, while that of sponge garden on the shallow ecosystem functioning remains uncertain.